The efficacy of the reading racetrack intervention in enhancing sight-word fluency among elementary students with reading difficulties - Alkinj, Issa; Alkinj, Othman; Al-Laimoun, Musab (International Journal of Innovative Research and Scientific Studies, 2025)
This study examines the effectiveness of combining the Reading Racetrack intervention with flashcards and positive reinforcement to enhance sight-word fluency in struggling third-grade readers. A multiple baseline design across participants (baseline, intervention, and maintenance) was employed to evaluate the intervention’s impact. Three students diagnosed with reading disabilities, aged 7 to 8 years, participated in the study. The results indicated that all participants demonstrated significant improvements in sight-word fluency and maintained the gains two weeks post-intervention. The participants and their teachers also rated the intervention as highly acceptable, feasible, and beneficial. We recommend exploring the effectiveness of the RRT intervention in home settings. Furthermore, we suggest comparing the efficiency of the RRT intervention versus the use of flashcards with social reinforcement to determine which technique yields more improvements in sight-word fluency.